Interactions of Cholecystokinin and Glutamatergic Systems in Feeding Behavior of Neonatal Chickens - M Jelokhani; B Vazir; M Zendehdel; A Jahandideh (Archives of Razi Institute, 2022)
This study aimed to assess the possible feeding behavior alterations by central interactions of cholecystokinin (CCK) and glutamatergic systems in neonatal chickens. In experiment 1, chickens received intracerebroventricular (ICV) administration of saline and CCK (CCK4; 0.25, 0.5, and 1 nmol). In experiment 2, birds were ICV injected with saline, CCK8s (0.25, 0.5, and 1 nmol). In experiment 3, chickens received the ICV injection of saline, CCK8s (1 nmol), MK-801 (15 nmol), and co-injection of the CCk8s+MK-801. Experiments 4-7 were performed similar to experiment 3, except for chickens that were injected with CNQX (390 nmol), AIDA (2 nmol), LY341495 (150 nmol), and UBP1112 (2 nmol) instead of MK-801. Subsequently, the total amount of the consumed food was determined. According to the results, the ICV administration of CCK4 (0.25, 0.5, and 1 nmol) could not affect the food intake in chickens (P>0.05). The ICV injection of the CCK8s (0.25, 0.5, and 1 nmol) led to a dose-dependent hypophagia (P<0.05). Moreover, hypophagia induced by CCK8s decreased by the co-injection of the CCK8s+MK-801 (P<0.05). These results showed that the hypophagic effects of the CCK on food intake can be mediated by NMDA glutamate receptors in layer-type chickens.